1997
DOI: 10.1046/j.1365-3083.1997.d01-135.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ Enhancement of E‐Selectin Expression on Endothelial Cells is Inhibited by Monensin

Abstract: Strindhall J, Lundblad A, Påhlsson P. Interferon-g Enhancement of E-Selectin Expression on Endothelial Cells is Inhibited by Monensin. Scand J Immunol 1997;46:338-343 The expression of E-selectin reaches a maximum 4-6 h after stimulation of human umbilical vein endothelial cells (HUVEC) in vitro with tumour necrosis factor-a (TNF-a) and then declines to basal level within 24 h. If interferon-g (IFN-g) is added to the cell culture medium together with TNF-a the surface expression of Eselectin is augmented an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…We found that TNF-a had a pronounced pro-inflammatory effect in HMVEC-Cs and also in HUVECs, whereas high glucose, insulin, IGF1 or IL6 did not affect E-selectin expression. Prominent effects of TNF-a on E-selectin expression have previously been shown in HUVECs and in human aortic endothelial cells (Strindhall et al 1997, Ewart et al 2008, Mako et al 2010. The lack of insulin or IGF1 effects is in agreement with observations made with HUVECs (Balaram et al 1997, Montagnani et al 2002, Madonna et al 2004.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that TNF-a had a pronounced pro-inflammatory effect in HMVEC-Cs and also in HUVECs, whereas high glucose, insulin, IGF1 or IL6 did not affect E-selectin expression. Prominent effects of TNF-a on E-selectin expression have previously been shown in HUVECs and in human aortic endothelial cells (Strindhall et al 1997, Ewart et al 2008, Mako et al 2010. The lack of insulin or IGF1 effects is in agreement with observations made with HUVECs (Balaram et al 1997, Montagnani et al 2002, Madonna et al 2004.…”
Section: Discussionsupporting
confidence: 90%
“…Expression of E-selectin was detected using an ELISA as described by Strindhall et al (1997). Briefly, HUVECs or HMVEC-Cs, 10 000 cells/well, were seeded in a 96-well microplate and incubated for 2 days.…”
Section: E-selectin Elisamentioning
confidence: 99%
“…First, IFN-g treatment affects processing of specific oligosaccharide side chains for some, but not all, transmembrane proteins. (32)(33)(34) Second, inhibitors of specific glycosylation processing steps alter the electrophoretic mobility for a3 integrin in a manner strikingly similar to those shown here. (35,36) Based on these two lines of evidence and lack of altered splicing in the carboxyl-terminal domain of the a3 subunit, our working hypothesis is that IFN-g may inhibit glycosylation of one or more of the integrin subunits.…”
Section: Discussionsupporting
confidence: 68%
“…Human umbilical vein endothelial cells (HUVEC) ELISA was performed according to the method described by Strindhall et al [17], with some modifications. Briefly, cells were grown in M199 medium in 96-well microtitre plates to a confluent cobblestone-like monolayer, and then incubated with TNF-α (40 ng/ml) for different periods of time (0, 2, 6 and 18 h).…”
Section: Quantitative Determination Of Muc1 By Measurement Of Incorpomentioning
confidence: 99%